Impact of Bolt Pretension on Bearing Strength for All-Steel Members and Composite Members - Liu, Jia-Hau; Bruneau, Michel (Engineering Journal, 2025)
Bolted connections are widely used in steel structures, and their design for slip-critical resistance and bearing strength is well documented in past research and current standards. However, the physical behavior that explains how friction and bearing forces interact in a pretensioned bolted connection and how these forces evolve under axial deformation remains unclear. This paper investigates the influence of bolt pretension on bearing strength through finite element analyses of both all-steel and composite splices [the latter one, of the type that would be found in composite plate shear walls/concrete filled (C-PSW/CF)]. The analyses captured the behavior of bolted connection, showing significant reduction in friction forces as bolt hole elongation increased. A simplified free-body diagram with contact springs was then employed to explain the yielding and bending of bolts, the loss of clamping forces, and the thinning of plates (due to the Poisson ratio effect), all of which contribute to the reduction of friction as hole elongation increases. Additionally, the study examines how bolt pretension affects C-PSW/CF connections under compression, showing that concrete restricts hole deformation and allows friction forces to be sustained until the concrete cracks and deformation progresses.